Natural history films generate more online interest in depicted species than in conservation messages - Grace Nolan; Adam Kane; Darío Fernández‐Bellon (People and Nature, 2022)
Abstract The greatest crises of our time are environmental. To combat the effects of climate change, biodiversity loss and environmental degradation will require the actions of all members of society. However, despite widespread consensus from the scientific community that human actions are driving this rapid environmental degradation, it remains unclear whether and to what extent the public is receiving and engaging with conservation messages. Natural history films have been suggested as one possible medium for generating awareness of conservation issues en masse but some environmental advocates have criticised these shows for lacking strong, focused conservation messaging. This study quantifies audience engagement with conservation themes and species depicted on screen in two BBC natural history super productions (Blue Planet II and Seven Worlds, One Planet) and a stand‐alone documentary with an explicit focus on conservation (Extinction: The Facts) by using big data analyses of Wikipedia page views during and after broadcast of each show and causal impact analysis. Our results indicate that natural history films are more effective at generating species awareness than transmitting conservation messages, but that audience engagement generated by conservation‐focused documentaries can be comparable to that generated by entire film series focused on natural history. With the ultimate goal of contributing to long‐term behavioural change, our results suggest that natural history films have the potential to drive mass audience engagement with conservation themes through better collaboration between filmmakers, conservationists and conservation messaging researchers. Finally, this study underscores how big data approaches can quantify the effectiveness of conservation messages across different mediums. Read the free Plain Language Summary for this article on the Journal blog.